Hybrid polymer-based photocatalytic materials for the removal of selected endocrine disrupting chemicals (EDCs) from aqueous media: a review - Mohd Hir, Zul Adlan; Abdullah, Abdul Halim (Elsevier, 2022)
The progress of hybrid polymer-based photocatalytic materials has captivated massive interest from researchers to expand the works of this specially fabricated material, exclusively for removing hazardous endocrine-disrupting chemicals (EDCs) in aqueous media. Several attractive features such as enormous pore structures, tunable band gap energy, excellent mechanical, chemical, and thermal properties with outstanding photoactivity and recyclability offer a new vision against traditional photocatalysts, which are ordinarily used in suspension mode. A deterioration in the freshwater reservoir is bearing notable domestic and industrial challenges. Nonetheless, their efficacy for the photo-removal of EDCs can be boosted by conducting surface or bulk modifications utilizing appropriate inorganic fillers for better interaction within the selected polymer matrix. This review discussed the performances of several hybrid polymer-based photocatalytic materials to eliminate distinct classes of EDCs and the implicated mechanism. The introduction of hybrid polymer-based photocatalytic materials in the water recovery process implies that developing the innovative protocol is obligatory for effectively removing EDCs from the ecosystem.